The Eyes Tell a Story: An Eye-Tracking Exploration on Metaphor Comprehension and Learning in Second Language Speakers of English - Aros Muñoz, Pablo (2023)
Despite the pervasiveness of metaphors in language, they are a challenging aspect of language comprehension. Many researchers have devoted their efforts to understand how people understand metaphors in a first language. However, not much research about the same process in a second language has been carried out. In this thesis, I delved into the comprehension process of metaphors and similes compared to literal sentences and explored how non-native speakers can learn metaphors in a second language. In Study 1, I used a reading task that presented native and non-native speakers with English metaphors and Spanish metaphors translated into English. In Study 2, native and non-native speakers were presented with metaphors, similes, and literal sentences. This study also involved a reading task in front of an eye-tracker that provided me with eye-movement data. The results of Study 2 showed a processing advantage of similes over metaphors due to the predictability that the word “like” adds to the sentences. Altogether, the results of these two studies point to a similar direction: it is more challenging to understand metaphors for native and non-native speakers than literal sentences. These two studies also provided supporting evidence to the role of familiarity and proficiency. First, study one showed that non-native speakers read L1 metaphors translated into the L2 faster than L2 metaphors. Second, Study 1 and 2 showed that higher levels of familiarity sped up the comprehension of metaphors for native and non-native speakers. Finally, Study 1 and 2 also showed that non-native speakers with higher levels of proficiency in the second language read metaphors – and similes – faster than their peers with lower levels of language proficiency. Following the findings from Study 1 and 2, I explored two ways in which non-native speakers could learn metaphors. In Study 3, I looked at the effect of implicit and explicit learning to metaphors in non-native speakers. In this study, which also used eye-tracking, participants were presented with metaphors embedded in naturalistic contexts and were assigned to one of the two learning conditions. Overall, participants in both learning conditions made similar learning gains, but participants in the explicit condition experienced a greater gain in the meaning recall task. The results in this thesis add valuable evidence to theories that look at metaphor comprehension in a second or foreign language. Under the right conditions, non-native speakers were able to quickly read metaphors. Non-native speakers benefit from high levels of proficiency and familiarity to quickly identify the non-literal meaning of metaphors. The results also showed that slow reading times may not reflect processing difficulty, but a lack of indication that the phrase being read entails finding similarities between the topic and the vehicle. Finally, this thesis also showed that non-native speakers were able to learn metaphors at great rates only after a few exposures in both explicit and implicit learning conditions.